Comparison of conventional chest physiotherapy and oscillatory positive expiratory pressure therapy in primary ciliary dyskinesia - KARADAĞ, BÜLENT TANER; ERDEM ERALP, ELA; GÖKDEMİR, YASEMİN (WILEY, 2020)
Background Chest physiotherapy (CP) is a recommended treatment modality in primary ciliary dyskinesia (PCD). Objective Primary aim was to compare the efficacy and safety of the conventional chest physiotherapy (CCP) and oscillatory positive expiratory pressure therapy (OPEPT). Secondary aims were to compare the exacerbation rate, time until the first exacerbation, patient compliance and comfort between the two CP methods. Methods This is a 6 month randomized, controlled crossover trial. Patients >6 years of age with PCD were randomized into two groups, first group was assigned to OPEPT (Acapella (R)) for 3 months while second group was assigned to CCP. Groups were crossed over to the other modality after a 15-day washout period. Pulmonary function tests (PFTs) and compliance were monitored by monthly clinic visits. Results There was a significant increase in FEV1, FEF25-75, and PEF values (p = .018,p = .020, andp = .016, respectively) in the OPEPT group and in FVC values (p = .007) in CCP group compared to baseline. However PFT increase at 3rd month was not superior to each other with both physiotherapy methods. Median acute pulmonary exacerbation rate and time period until the first exacerbation were similar in both groups (p = .821,p = .092, respectively). Comfort and effectiveness of OPEPT was higher than CCP according to patients (p = .029 andp = .042, respectively). There were no adverse effects with either therapy. Conclusions OPEPT was as effective as CCP in PCD patients. OPEPT was more comfortable and effective than CCP according to patients. OPEPT might be an efficient alternative method for airway cleareance in PCD patients.
Keywords: chest physiotherapy; oscillatory positive expiratory pressure therapy; primary ciliary dyskinesia; RANDOMIZED CROSSOVER TRIAL; AIRWAY-CLEARANCE THERAPY; QUALITY-OF-LIFE; CYSTIC-FIBROSIS; FLUTTER DEVICE; BRONCHIECTASIS; VALIDATION; INSTRUMENT; ADHERENCE; CHILDREN